2008
DOI: 10.1515/cclm.2008.012
|View full text |Cite
|
Sign up to set email alerts
|

A new high-throughput screening method for the detection of chronic lymphatic leukemia and myelodysplastic syndrome

Abstract: Based on their high predictive value, research population data could be routinely used to screen for chronic lymphatic leukemia and myelodysplastic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 9 publications
1
22
1
Order By: Relevance
“…The haematology analysers can measure some positional parameters of the different cell populations in PB that can be useful in the identification of some pathologies, such as granulocytic dysplasia or sepsis . Furthermore, some papers suggest that lymphocyte positional parameters can be useful to differentiate viral diseases (VD) from lymphoproliferative disorders, as well as to detect the presence of Sézary cells or mantle cell lymphoma cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The haematology analysers can measure some positional parameters of the different cell populations in PB that can be useful in the identification of some pathologies, such as granulocytic dysplasia or sepsis . Furthermore, some papers suggest that lymphocyte positional parameters can be useful to differentiate viral diseases (VD) from lymphoproliferative disorders, as well as to detect the presence of Sézary cells or mantle cell lymphoma cells …”
Section: Introductionmentioning
confidence: 99%
“…The haematology analysers can measure some positional parameters of the different cell populations in PB that can be useful in the identification of some pathologies, such as granulocytic dysplasia or sepsis. [1][2][3][4] Furthermore, some papers suggest that lymphocyte positional parameters can be useful to differentiate viral diseases (VD) from lymphoproliferative disorders, [5][6][7][8][9] as well as to detect the presence of Sézary cells 10 or mantle cell lymphoma cells. 11 The aim of our study was to investigate the usefulness of the lymphocyte positional parameters in the Sysmex XN haematology analyser to detect changes in the lymphocytes and differentiate among the various lymphoproliferative disorders, mononucleosis syndrome (MNS) and other non-neoplastic lymphocytoses.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that patients with MDS showed significantly lower levels of both neutrophil mean cell scatter and mean cell conductivity than healthy controls in research population data, and concluded that these parameters were especially useful for the screening of neutrophil dysplasia, such as hypogranularity. Haschke-Becher et al [23] also examined 19 patients with MDS using LH 750, and concluded that standard deviations of neutrophil conductivity were most predictive of MDS. We have also reported that the CELL-DYN 3500 hematology analyzer could provide useful neutrophil distribution patterns for the screening of patients with MDS using 2 characteristic light scatters [12].…”
Section: Discussionmentioning
confidence: 99%
“…The value of NE-SSC, NE-SFL, NE-FSC, NE-WX, NE-WY, and NE-WZ varies in healthy and ill population and can be investigated as an important predictive marker in different hematological malignancies. There are some emerging data on the utilization of these non-reportable research parameters in sepsis 6-10 , myelodysplastic syndrome [11][12][13][14][15] , and severe infections [16][17][18][19] . Studies concluded that such biomarkers might provide useful information for the early diagnosis and adequate management of these disorders.…”
Section: Introductionmentioning
confidence: 99%